EXAMINING SOCIAL PRESENCE IN ONLINE COURSES IN RELATION TO STUDENTS' PERCEIVED LEARNING AND SATISFACTION - Richardson, Jennifer C.; Swan, Karen (Online Learning, 2003)
Research has demonstrated that social presence not only affects outcomes but also student, and possibly instructor, satisfaction with a course. Teacher immediacy behaviors and the presence of others are especially important issues for those involved in delivering online education. This study explored the role of social presence in online learning environments and its relationship to students’ perceptions of learning and satisfaction with the instructor. The participants for this study were students who completed Empire State College’s (ESC) online learning courses in the spring of 2000 and completed the end of semester course survey (n=97). A correlational design was utilized. This study found that students with high overall perceptions of social presence also scored high in terms of perceived learning and perceived satisfaction with the instructor. Students’ perceptions of social presence overall, moreover, contributed significantly to the predictor equation for students’ perceived learning overall. Gender accounted for some of the variability of students’ overall perception of social presence, while age and number of college credits earned did not account for any of the variability.